Synthesis of New Phosphonoamide and Phosphonocaprolactam Derivatives via the Diethyl Chlorophosphate‐Promoted Beckmann Rearrangement of γ‐Phosphonyloximes. Issue 6 (23rd June 2015) - Wahbi, Aymen; Touil, Soufiane
ABSTRACT: Herein, we report an efficient and straightforward synthesis of new phosphonoamide and phosphonocaprolactam derivatives, via the Beckmann rearrangement of γ‐phosphonyloximes. The reaction proceeded smoothly in the presence of diethyl chlorophosphate as a promoter, to afford the title compounds in satisfactory yields. A mechanistic rationalization for this reaction is provided allowing for the prediction of its regiochemistry.